PENINGKATAN HASIL BELAJAR PSIKOMOTORIK KEGIATAN KEAGAMAAN MELALUI KETERLIBATAN SISWA - Afifah, Afifah; Mashuri, Imam (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
Improving psychomotor learning outcomes in religious activities is an obligation that must be achieved by students in every basic competency in Islamic Religious Education subjects where a curriculum is implemented that requires students to be able to display their skills. The researcher intends to reveal 1. What are the psychomotor learning outcomes of students' religious activities? 2. How students' involvement in religious activities improves psychomotor learning outcomes. 3. What are the supporting and inhibiting factors for improving psychomotor learning outcomes in religious activities through student involvement. Researchers have three goals. 1. To find out what the psychomotor learning outcomes of students' religious activities are. 2. To find out how student involvement in religious activities improves psychomotor learning outcomes. 3. To find out what are the supporting and inhibiting factors for improving learning outcomes in psychomotor activities through student involvement. This research uses a phenomenological approach and an inductive qualitative research type. The data collection technique used by the author is using interviews, observation and documentation methods and the validity of the data used is using triangulation of sources, techniques and time. The research results show that: 1. The psychomotor learning outcomes applied consist of: Planning, implementation, follow-up, techniques and instruments for psychomotor learning outcomes, increasing Psychomotor Learning Outcomes. 2. Student Involvement in Religious Activities in Improving Psychomotor Assessment consists of: Students Practicing as Friday Prayer Prayers, Student Involvement in BTAQ Activities. 3. Supporting and inhibiting factors in improving psychomotor learning outcomes in religious activities through student involvement include: Supporting Factors, namely the school fully supports both from within (school activities) and outside (family). Inhibiting Factors, namely inadequate infrastructure and insufficiently long PAI learning hours.